Will the use of cashless subsidy potentially reduce illegal underground economy activity? A case study in Indonesia - Wibowo, Joshi Maharani; Hariadi, Sugeng (Business, Management and Economics Engineering, 2025)
Purpose – This study was conducted to understand the potential of cashless subsidy to reduce illegal underground economy activity in Indonesia. Research methodology – The research was done through a qualitative approach then analyzed based on the content analysis and sentiment analysis using Digital Public Services Index frim Digital Economy and Society Index (DESI) research methodology as base. The data used on this study are Indonesia e-news on kompas.com, detik.com, and tempo.co from March 2021- 2022 using two keywords “subsidi” (subsidy), “non-tunai” (cashless) and “nirsentuh” (contactless). Findings – The result of this study shows illegal underground economy activity can be reduced by implementing cashless subsidy policy. Research limitations – The data used on the research were big data obtained from e-news be- cause the lack primary reliable respondent. We could not estimate the cashless subsidy after COVID-19 was ended in Indonesia because the declaration of the end of COVID-19 pandemic in Indonesia was on 29 June 2023. Practical implications – This study also provides two recommendations for those problems: (a) increase digital financial literacy awareness; (b) improve the formal economy activity. Originality/Value – There still no specific research of cashless subsidy and their practice in shad- ow economy perspective, especially in developing countries such as Indonesia.